Otimização multiobjetivo de lajes nervuradas em concreto armado - Bezerra, Eric Mateus Fernandes (2017)
Reinforced concrete ribbed slabs are more suitable than conventional concrete slabs when applied in large gaps. However, the minimum dimensions of this system have been modified, leading to questioning its efficiency. In order to verify the economic efficiency of the shape patterns usually adopted in the design of ribbed slabs, this work presents a multiobjective optimization model of reinforced concrete ribbed slabs, in accordance with the standards NBR 6118/2014 and NBR 15575/2013. The multiobjective optimization is related to the application of the NSGA II algorithm for the minimization of the economic cost and CO2 emission and for the minimization of the cost and maximization of the natural frequencies, according to the design restrictions. The design variables are rib width, depth of rib, ribs spacing, the top slab thickness, reinforcement steel and compressive strength of the concrete. The grillage analysis, which has led to satisfactory results in the design of this type of slab, was used in the structural analysis of slabs. The proposed methodology was based on the equivalent thickness concept to decouple the optimization model from grid mesh generation. The results showed that the change in the minimum dimensions resulted in an increase of 37.5% of the average cost. In addition, the results indicate that the economic cost and CO2 emission are closely related, which indicates that minimizing the cost will be obtained a good environmental solution.